Digital Supply Chain Optimization in E-Commerce Bubiess Beads Using The Simplex Method Based On Coefficient Matrix - Nabilla Alya Naila; Najwa Fauziah; Nurhalimah; Naufal Ihsan Hadi Mukhtar; Loranty Folia Simanjuntak (Outline Publisher, 2026)
Purpose: Differences in raw material shipping costs from multiple suppliers can increase production costs for small e-commerce businesses, especially handmade product businesses reliant on multi-source procurement. This issue is also experienced by bubiess.beads in determining the most efficient supplier. This study aims to determine optimal raw material procurement decisions to minimize production costs while maximizing monthly production profit. Methods: A mathematical model representing the relationship between decision variables and procurement constraints in coefficient matrix form was developed, combining supplier consolidation through cost minimization and production mix optimization through profit maximization, both solved using the simplex method. Results: Consolidating procurement to a single supplier reduced total costs from Rp131,900 to Rp114,700 per month through a 75.9% reduction in shipping fees. The optimal production mix of 15 units each for bracelets, necklaces, and accessories generated maximum profit of Rp817,500 per month, an 11.2% improvement over pre-optimization conditions. Conclusions: The model provides more efficient procurement decision alternatives, reducing production costs and supporting supply chain decision-making in small-scale e-commerce businesses. Originality/value: This study introduces an integrated two-model approach combining supplier selection and production mix optimization within a coefficient matrix framework, applied to a handmade accessory MSME operating through digital supply chains, an underexplored context in existing operations research literature.